TUNNELING PROPERTIES OF HETEROSTRUCTURES WITH A DOUBLE MAGNETIC BARRIER - A. N. Kocharian; A. S. Sahakyan; R. M. Movsesyan
We consider the spin-dependent transport properties of an unpolarized electron beam through a multilayer system containing two magnetic barriers with different orientations of magnetizations. The dependences of the transmission coefficient and degree of polarization of transmitted electrons on the angle between the magnetization vectors of barriers and energy of electrons are calculated using transfer-matrix approach. It is found that at the resonance tunneling this dependence should manifest itself quite strongly.
Keywords: Physics; Electronic structure and electrical properties of surfaces